Cortical gray matter volume and working memory in a NHP model of AD‐like neuropathology. (December 2021) - Frye, Brett M.; Craft, Suzanne; Register, Thomas C.; Kim, Jeongchul; Whitlow, Christopher T.; Barcus, Richard A.; Lockhart, Samuel N.; Solingapuram Sai, Kiran K.; Shively, Carol A.
Abstract: Background: Age‐related neurodegeneration characteristic of late‐onset Alzheimer's disease (LOAD) begins in middle age, well before symptoms. Therefore, translational models to identify modifiable risk factors in middle‐age are needed to understand the etiology and identify early therapeutic targets for intervention. Vervet monkeys ( Chlorocebus aethiops sabaeus ), like humans, have complex central nervous systems and naturally develop several risk factors for LOAD with age, including obesity, prediabetes, hypertension and decline in physical function. Furthermore, aged vervets also recapitulate many of the characteristics of early AD that are associated with reduced brain volumes, including human‐like Aβ accumulation in the brain, greater Aβ plaque burden, and reduced CSF Aβ. Thus, these NHPs are ideal models for studying healthy versus neuropathological aging. Method: Using structural magnetic resonance imaging and cognitive assessments, we examined the relationships between age, working memory, and neuroanatomy by measuring the thicknesses and volumes of AD‐signature cortical regions of interest ("meta‐ROIs") in 46 middle‐aged to elderly female vervets (8‐29 years of age). Result: Using linear mixed effects models with age as a fixed effect and individual as a random effect, we found that cortical gray matter volume significantly decreased with increasing age (β=‐51.94, SE=14.37; t=‐3.61; p<0.001). The thickness of the AD‐signature meta‐ROIs was not affected by age (β<0.01, SE<0.01; t=‐0.19; p=0.85), however, the volumetric meta‐ROI tended to decline with age in older animals (β=‐6.95, SE= 4.20; t=‐1.65; p= 0.098). In the precuneus, a component region of the meta‐ROI that has been shown to be reduced in preclinical AD, volume decreased with increasing age (β=‐1.69, SE=0.72; t=‐2.36; p= 0.023). In addition to these age‐related effects, the volume of the AD‐signature meta‐ROI was positively correlated with performance on the delayed response test of working memory (R= 0.235; p=0.026). Conclusion: Taken together, these findings demonstrate that cortical gray matter diminishes with age in vervet monkeys in regions relevant to AD risk, and is associated with cognitive impairment. This study provides important insights about the relationships between age, neuroanatomy, and memory in vervets, and lays the groundwork for future investigations to identify at‐risk phenotypes such that therapeutic interventions may be tested in this nonhuman primate model.